Decompressive hemicraniectomy for malignant middle cerebral artery infarction including patients with additional involvement of the anterior and/or posterior cerebral artery territory: outcome analysis and definition of prognostic factors - Kürten, Sven; Perrin, Jason Michael (Acta neurochirurgica, 2018)
According to current evidence, adding decompressive craniectomy (DC) to best medical therapy reduces case fatality rate of malignant middle cerebral artery infarction by 50-75%. There is currently little information available regarding the outcome of subgroups, in particular of patients with extensive infarctions exceeding the territory of the middle cerebral artery.